2021
DOI: 10.1002/advs.202102466
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Theranostic Nanomaterials in Diabetes and Its Complications

Abstract: Diabetes mellitus (DM) refers to a group of metabolic disorders that are characterized by hyperglycemia. Oral subcutaneously administered antidiabetic drugs such as insulin, glipalamide, and metformin can temporarily balance blood sugar levels, however, long‐term administration of these therapies is associated with undesirable side effects on the kidney and liver. In addition, due to overproduction of reactive oxygen species and hyperglycemia‐induced macrovascular system damage, diabetics have an increased ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 364 publications
(572 reference statements)
0
48
0
Order By: Relevance
“…In view of above‐mentioned micro‐environment, delivery platforms with intrinsic anti‐inflammatory and antioxidant properties are deemed promising candidates for reinforced effects to address diabetic wound 50,51 . Studies have indicated the antioxidant ability of DNA due to its deoxyribonucleotide nature 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…In view of above‐mentioned micro‐environment, delivery platforms with intrinsic anti‐inflammatory and antioxidant properties are deemed promising candidates for reinforced effects to address diabetic wound 50,51 . Studies have indicated the antioxidant ability of DNA due to its deoxyribonucleotide nature 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, delayed wound healing and chronic wound infection are important health concerns faced by diabetic patients and improvement in their treatment is highly desired. 2–4…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have made great efforts in the development of new therapeutic techniques. 7,22,23 For example, many functional therapeutic systems based on nanomaterials, films, and hydrogels have been developed. [24][25][26][27] Besides, to protect the bioactivity of drugs, improve the therapeutic effect and minimize the side effects of different treatment strategies, responsive therapeutic systems have been employed for the spatiotemporal control of drug delivery/activation, which exhibit excellent performance in the treatment of diabetic infected wounds.…”
Section: Introductionmentioning
confidence: 99%